Humoral immune responses to testis antigens in sera from patients with prostate cancer - Hoeppner, Luke H; Dubovsky, Jason A; Dunphy, Edward J; McNeel, Douglas G (Cancer immunity, 2006)
Tumor vaccines represent one type of molecularly targeted therapy being investigated for the treatment of prostate cancer. Although many prostate-specific proteins are being tested as target antigens for prostate cancer vaccines, most are not natural targets of an immune response in patients with cancer. Using sera from cancer patients, several research groups have identified a large family of immunologically recognized proteins whose expression is normally confined to immune-privileged testis tissue but which may be expressed in cancers of different histological origins. These proteins, so-called cancer-testis (CT) antigens, are appealing targets for immune-based therapies because they are essentially tumor-restricted antigens and there is less risk of preexisting immune tolerance. In addition, specifically targeting these proteins by means of vaccines should reduce the risk of potential autoimmune reactions to normal tissues. In the current study, we hypothesize that prostate CT antigens can be identified using a SEREX screening method with sera from patients with prostate cancer and probing with a human testis cDNA expression library. We have identified several potential prostate cancer antigens with predominantly testis-specific expression in normal tissues, including MAD-CT-1 (protamine 2) and MAD-CT-2. Each was independently identified from different subjects with prostate cancer. Antigens identified by these studies can be investigated further as potential prostate cancer tumor antigens.